Type Synthesis of the Mechanism of Pulse CVT based on Kinematic Chain - Song Zhongkang; Bai Lianqiang; Wang Peng (Jixie chuandong)
According to the topology configuration of the existing pulse CVT,the design requirements of the pulse CVT are summarized and the kinematic chain satisfying the design requirements is calculated by the combination. The structure and motion pair of the found kinematic chain are weighted one by one. A variety of new and some existing pulse CVT mechanism configurations are obtained,which proves the validity and rationality of the type synthesis method and the new configuration based on the kinematic chain. A pulse CVT based on the gear linkage combined mechanism is preferably selected as a preferred mechanism from the plurality of new configurations.